Analysis of the costs and logistics of biodiesel production from used cooking oil in the metropolitan region of Campinas (Brazil). (May 2018) - Miranda, Amanda Carvalho; da Silva Filho, Silvério Catureba; Tambourgi, Elias Basile; CurveloSantana, José Carlos; Vanalle, Rosangela Maria; Guerhardt, Flávio
Abstract: The Brazilian Petroleum Regulatory Agency (ANP) regulates the use of biodiesel in fuel oil throughout Brazil. Current laws require that from 2017, diesel oil must contain 8% biodiesel (i.e., B8). In fact, the bus fleets of some Brazilian regions already use the B20 blend (20% biodiesel) as fuel. The objective of this work was to analyse the costs and logistics of biodiesel production from mixtures of used cooking oils in the Metropolitan Region of Campinas (RMC, São Paulo State, Brazil). Cooking oils collected from MRC homes were mixed with ethanol in various proportions and transesterified at 60 °C for 30 or 90 min, in order to obtain biodiesel, using NaOH as a catalyst. The results of the physical and chemical analyses demonstrated that the biodiesels so obtained possessed characteristics close to those required by Brazilian standards. This fuel could be used in fleets of buses, trucks and machines, or even sold to fuel distributors; and would be worth 15.784 million USD/year. Thus, MRC would gain environmental credits and become a sustainable city. As part of a logistical planning proposal to collect used cooking oils during household garbage collection in MRC, an idea was presented for a reservoir attached to garbage trucks. Two or more companies might work together to create a competitive advantage and higher profits than could be achieved by unitary action. The biodiesel industrial plant must be placed in Barão Geraldo District, which is near a petroleum refinery in Paulínia as well as highways of national importance and pharmaceutical industries. The reduction of more than 20% in all emissions of greenhouse gases and particulate matter has been proven since implementation of the current policy requiring the use of biodiesel in the region's bus fleet.